2014
DOI: 10.1155/2014/780410
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antifungal Activity against Oral Candida Species Using a Denture Base Coated with Silver Nanoparticles

Abstract: Although oralCandidaeasily adheres to denture base materials, many denture detergents are effective only against bacteria but not againstCandida. Silver nanoparticles (AgNPs), which are known to have potent antibacterial and antifungal activity, have been used in the prevention of oral candidiasis (OC). We evaluated the adherence ofCandida albicansandCandida glabrataon a heat-cured Acron resin piece supported by AgNPs by low-vacuum scanning electron microscopy (SEM) and measuring colony-forming units.C. albica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 19 publications
2
16
0
1
Order By: Relevance
“…These results are in agreement with previous study results that shown potent antifungal effects of AgNPs coating of denture base material -morphology deformation and inhibition of Candida adherence [26].…”
Section: Discussionsupporting
confidence: 94%
“…These results are in agreement with previous study results that shown potent antifungal effects of AgNPs coating of denture base material -morphology deformation and inhibition of Candida adherence [26].…”
Section: Discussionsupporting
confidence: 94%
“…When the inhibition effect of NmSAg coating on glass slabs against C. glabrata strain's, biofilm formation was examined; 20.9% inhibition was observed ( Fig. 1) and similar to our result, AgNPs are generally indicated to inhibit the adhesion of Candida to the denture surface according to the literature and are known to have an important role in preventing Candidarelated biofilm formation in the oral cavity (26,27).…”
Section: Resultssupporting
confidence: 85%
“…Applying a coating resin to the denture surface not only improves the mechanical and chemical properties of the material, but also demonstrates beneficial factors, such as biological resistance to oral pathogens and color change resistance [ 3 ]. Previous studies on the surface modification of acrylic resin-based materials have been continuously undertaken, postulating the inhibition of growth and the death of oral pathogenic microorganisms [ 46 , 47 , 48 , 49 ]. In addition, numerous studies have attempted to inhibit the attachment of microorganisms to material surfaces [ 50 ].…”
Section: Discussionmentioning
confidence: 99%